Preparation method and application of CoNi LDH-coated SnO2-coated Bi2O2CO3 oxide composite catalyst
By constructing a multi-layer CoNi LDH@SnO2@Bi2O2CO3 oxide composite catalyst, the problem of insufficient performance optimization and stability of multi-component catalysts in the electrolytic hydrogen production process is solved, and the effect of efficient electrolytic hydrogen production is achieved.
Patent Information
- Application Number
- CN202510602070.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-12
- Publication Date
- 2025-08-12
AI Technical Summary
In the process of electrolyzing hydrogen production with existing multi-component catalysts, the catalytic performance optimization and stability are insufficient, especially under harsh conditions such as high temperature and high sulfur. The cost of precious metal catalysts is high and difficult to apply on a large scale.
CoNi ZIF is used as the template to construct a multi-layer CoNi LDH@SnO2@Bi2O2CO3 oxide composite catalyst by multi-step hydrothermal method to form a unique heterointerface. The positive and negative ion alternating structure of Bi2O2CO3 is used to accelerate electron transport and charge transfer, and improve catalytic activity and stability.
It improves the electrochemical performance and chemical stability of the catalyst, reduces the difficulty of preparation, and realizes an efficient electrolysis hydrogen production process, which is suitable for complex reaction systems.
Smart Images

Figure CN120465049A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a preparation method and application of a CoNi LDH@SnO2@Bi2O2CO3 oxide composite catalyst, belonging to the technical field of electrocatalysis. Background Art
[0002] The direct production of hydrogen by electrolysis of water has the advantages of high hydrogen purity, pollution-free products, widely available raw materials, and simple preparation process.
[0003] How to improve catalyst performance, reduce reaction overpotential, and greatly reduce the energy consumption of water electrolysis will be one of the key areas of focus in the future. Precious metals have excellent performance in electrocatalytic hydrogen production, but are difficult to promote on a large scale due to their high cost and low reserves. Transition metals and their derivatives have high electrocatalytic activity, and their costs can be reduced by multiples compared to precious metals, but there is still a large gap in single metals and optimization strategies in improving catalyst activity. Multi-component alloys and multi-strategy collaborative optimization can effectively improve the catalytic activity of materials. The unique heterogeneous interface can accelerate the adsorption and conversion of ions, while accelerating the desorption of gases, increasing the contact interface and time between the catalyst and water, and thus accelerating the hydrogen production rate.
[0004] In the prior art, multi-component catalysts have certain application value, but the interaction mechanism between the components in multi-component catalysts is currently difficult to accurately grasp and regulate, resulting in challenges in catalyst performance optimization and reproducibility. Factors such as the order of addition and distribution of different components may have a significant impact on catalytic performance, increasing the complexity and uncertainty of the preparation process. In addition, during the preparation process of multi-component catalysts, it is difficult to achieve an ideal dispersion of active ingredients on the carrier. If the active ingredients are unevenly distributed, some areas may be too active and easily adsorb other impurities, leading to deactivation, while other areas may be insufficiently active, and the overall performance of the catalyst cannot be fully utilized. At the same time, although multi-component catalysts have strong stability to a certain extent, their stability still needs to be improved under some harsh reaction conditions, such as high temperature and high sulfur environments. Active components may agglomerate at high temperatures, resulting in a reduction in active surface area, and insufficient tolerance to certain poisons will affect the activity and life of the catalyst.
[0005] The multi-interface construction of composite catalysts, through the combination of different materials and interlayer design, allows for more precise preparation methods and structural regulation, better control over the distribution and interactions of the components, and precise regulation of catalyst performance, thereby overcoming some of the shortcomings of multi-component catalysts in terms of performance regulation and stability. Compared with the design and regulation of multi-catalyst composite interfaces, element doping can only achieve limited performance adjustments for a single catalyst, making it difficult to meet the increasingly complex structural and performance requirements of catalysts. Composite catalysts can combine materials with different functions to achieve functional integration and synergistic effects, making them more suitable for the requirements of complex reaction systems. This synergistic effect is difficult to achieve with single catalysts through element doping. The study of composite catalysts provides opportunities for the discovery of new catalytic phenomena and mechanisms. In addition, the combination of different materials may produce unique physicochemical properties and interfacial effects. These new characteristics have the potential to promote breakthroughs in catalyst performance and provide new ideas and approaches for the development of high-performance catalysts. Summary of the Invention
[0006] To address the performance control and inadequate stability issues of existing multi-component alloys, this paper proposes a method for preparing and applying a CoNiLDH@SnO2@Bi2O2CO3 oxide composite catalyst. Using a CoNi ZIF as a template, a multi-step hydrothermal method is used to construct multiple catalytic interfaces, resulting in a multilayer CoNi LDH@SnO2@Bi2O2CO3 oxide composite electrocatalyst. This unique heterogeneous interface accelerates gas conversion and desorption. Furthermore, the unique layered structure of Bi2O2CO3, with alternating positive and negative ions, facilitates interlayer adsorption and transport of electrons, accelerating charge transfer. This method can increase the number of catalytically active sites, reduce the difficulty of catalyst preparation, and enhance the electrochemical performance and chemical stability of the composite catalyst.
[0007] A preparation method of CoNi LDH@SnO2@Bi2O2CO3 oxide composite catalyst, the specific steps are as follows:
[0008] (1) dissolving nickel nitrate and ferric nitrate in deionized water to obtain a nickel-iron solution, and dissolving dimethylimidazole in deionized water to obtain a dimethylimidazole solution;
[0009] (2) slowly adding the dimethylimidazole solution to the nickel-iron solution under stirring for 10 to 30 minutes, separating the solid and the liquid, and drying the solid to obtain CoNi-ZIF powder;
[0010] (3) CoNi-ZIF powder was uniformly dispersed in deionized water to obtain a CoNi-ZIF dispersion, SnCl4·5H2O and hexamethylenetetramine were added to the CoNi-ZIF dispersion, stirred for 2-4 h, and then subjected to hydrothermal reaction at 180-200°C for 6-14 h. The solid-liquid separation was performed, and the solid was washed with anhydrous ethanol and then dried to obtain CoNi LDH@SnO2 powder;
[0011] (4) The CoNi LDH@SnO2 powder was ultrasonically dispersed in deionized water to obtain a CoNi LDH@SnO2 dispersion. Bi(NO3)3·5H2O, hexamethylenetetramine and sodium citrate were added to the CoNiLDH@SnO2 dispersion, and the mixture was stirred and reacted at a temperature of 60-80°C for 2-4 h. The mixture was then placed at a temperature of 140-180°C for hydrothermal reaction for 5-10 h. The solid-liquid separation was carried out, and the solid was dried to obtain the CoNi LDH@SnO2@Bi2O2CO3 oxide composite catalyst.
[0012] Preferably, in step (1), the mass ratio of cobalt nitrate, nickel nitrate and dimethylimidazole is 1:0.5-0.25:15-20, the concentration of cobalt nitrate in the cobalt-nickel solution is 0.004-0.008 g / mL, the concentration of nickel nitrate is 0.002-0.001 g / mL, and the concentration of dimethylimidazole solution is 0.06-0.08 g / mL.
[0013] Preferably, the concentration of the CoNi-ZIF dispersion in step (3) is 0.004-0.002 g / mL, the mass ratio of SnCl4·5H2O to CoNi-ZIF powder is 20-10:1, and the molar ratio of hexamethylenetetramine to SnCl4·5H2O is 0.5-0.6:1.
[0014] Preferably, the concentration of the CoNi LDH@SnO2 dispersion in step (4) is 0.004-0.002 g / mL, the mass ratio of Bi(NO3)3·5H2O, sodium citrate and CoNi LDH@SnO2 powder is 2.5-6:2-5:1, and the molar ratio of hexamethylenetetramine to Bi(NO3)3·5H2O is 2.5-7.5:1.
[0015] The CoNiLDH@SnO2@Bi2O2CO3 oxide composite catalyst is used as a catalyst in hydrogen production by water electrolysis.
[0016] The principle of high electrochemical performance and chemical stability of the CoNi LDH@SnO2@Bi2O2CO3 oxide composite catalyst: First, the ZIF template method is used to prepare the CoNi LDH catalyst matrix, and the advantages of the LDH catalyst such as layered structure, adjustable interlayer anions, large specific surface area, and uniform grains are used to provide rich active sites for the catalyst. The interaction between Co and Ni can adjust the electronic structure of the catalyst. The layered structure of LDH can also prevent the agglomeration of nanoparticles and increase the stability of the catalyst. The middle layer SnO2, as an n-type semiconductor, has good electron transport properties and can quickly transfer the electrons generated by CoNi LDH to the outer layer Bi2O2CO3, promoting the separation of electrons and holes. At the same time, the oxygen vacancies on the SnO2 surface can adsorb and activate oxygen molecules, thereby improving the catalytic activity of the catalyst for oxygen reduction reactions. The outermost layer Bi2O2CO3 also has a unique layered structure (Bi2O2 2+ Positive ion layer and CO 3- Negative ion layer) and energy band structure, giving it good catalytic performance and electrochemical activity. Bi2O2CO3 can form a heterojunction with SnO2, further promoting the separation and migration of electron-hole pairs and improving the overall performance of the catalyst.
[0017] Conventional doping usually involves incorporating one or several elements into a single matrix material to change its electronic structure and catalytic performance. The CoNiLDH@SnO2@Bi2O2CO3 composite catalyst is designed with a multilayer structure, which creates a strong synergistic effect between the different components. This synergistic effect is not only reflected in the electron transport and adsorption properties, but also in the activation and conversion ability of the different components on the reaction intermediates. Compared with conventional doping, it can significantly improve the electrochemical performance and chemical stability of the catalyst. At the same time, due to its multilayer structure and the presence of multiple components, the composite catalyst can not only be used in fields such as electrocatalysis and photocatalysis, but also exhibit good activity and selectivity under different reaction conditions, and has a wider application prospect than conventional doping.
[0018] The beneficial effects of the present invention are:
[0019] (1) The present invention uses CoNi ZIF as a template and constructs multiple catalytic interfaces through a multi-step hydrothermal method to prepare a multi-layer CoNi LDH@SnO2@Bi2O2CO3 oxide composite electrocatalyst. The synergistic effect of multiple metals in the multi-alloy layered metal hydroxide is beneficial to improving the material conductivity and accelerating electron transport. The layered structure of the layered metal hydroxide has a large specific surface area and effectively provides active sites.
[0020] (2) The SnO2 layer in the present invention can accelerate electron transport, facilitate the adsorption of O intermediates, and construct a multilayer semiconductor structure that can accelerate the transmission and transfer of charges and accelerate the conversion of intermediates;
[0021] (3) The Bi2O2CO3 of the present invention has a unique structure in which positive and negative ion layers are arranged alternately, which can improve the adsorption of OH- on the surface and provide a high-speed channel for electron transmission between layers. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is the XRD pattern of the CoNi LDH@SnO2@Bi2O2CO3 composite catalyst in Example 1;
[0023] Figure 2 SEM image of CoNi ZIF;
[0024] Figure 3 This is the SEM image of the Bi2O2CO3 sample;
[0025] Figure 4 is the SEM image of SnO2 sample;
[0026] Figure 5 This is the SEM image of the CoNi LDH@SnO2@Bi2O2CO3 composite catalyst in Example 1;
[0027] Figure 6 Polarization curves of the CoNi LDH@SnO2@Bi2O2CO3 composite catalyst in Example 1 and the catalysts in Comparative Examples 7 and 8. DETAILED DESCRIPTION
[0028] The present invention will be further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the contents described above.
[0029] Example: A method for preparing a CoNi LDH@SnO2@Bi2O2CO3 oxide composite catalyst, the specific steps are as follows:
[0030] (1) dissolving nickel nitrate and ferric nitrate in deionized water to obtain a nickel-iron solution, and dissolving dimethylimidazole in deionized water to obtain a dimethylimidazole solution; the mass ratio of the cobalt nitrate, nickel nitrate, and dimethylimidazole is 1:0.5-0.25:15-20, the concentration of cobalt nitrate in the cobalt-nickel solution is 0.004-0.008 g / mL, the concentration of nickel nitrate is 0.002-0.001 g / mL, and the concentration of the dimethylimidazole solution is 0.06-0.08 g / mL;
[0031] (2) Under stirring conditions, the dimethylimidazole solution was slowly added to the nickel-iron solution for 30 minutes, and the solid-liquid separation was performed. The solid was dried to obtain CoNi-ZIF powder (denoted as powder A);
[0032] (3) CoNi-ZIF powder was uniformly dispersed in deionized water to obtain a CoNi-ZIF dispersion, SnCl4·5H2O and hexamethylenetetramine were added to the CoNi-ZIF dispersion, stirred for reaction for 2 h, and then subjected to hydrothermal reaction at a temperature of 180-200°C for 6-14 h. The solid-liquid separation was performed, and the solid was washed with anhydrous ethanol and then dried to obtain CoNi LDH@SnO2 powder (denoted as powder B); the concentration of the CoNi-ZIF dispersion was 0.002-0.004 g / mL, the mass ratio of SnCl4·5H2O to CoNi-ZIF powder was 20-10:1, and the molar ratio of hexamethylenetetramine to SnCl4·5H2O was 0.5-0.6:1;
[0033] (4) CoNi LDH@SnO2 powder was ultrasonically dispersed in deionized water to obtain CoNi LDH@SnO2 dispersion, Bi(NO3)3·5H2O, hexamethylenetetramine and sodium citrate were added to the CoNiLDH@SnO2 dispersion, stirred and reacted at 80℃ for 2h, and then placed at 140-180℃ for hydrothermal reaction for 5-10h, solid-liquid separation was performed, and the solid was dried to obtain CoNi LDH@SnO2@Bi2O2CO3 oxide composite catalyst (denoted as powder C); the concentration of CoNi LDH@SnO2 dispersion was 0.002-0.004g / mL, the mass ratio of Bi(NO3)3·5H2O, sodium citrate and CoNi LDH@SnO2 powder was 2.5-6:2-5:1, and the molar ratio of hexamethylenetetramine to Bi(NO3)3·5H2O was 2.5-7.5:1;
[0034] The specific parameters in Examples 1 to 5 are shown in Table 1 below.
[0035] Table 1 Process parameters of Examples 1 to 5 (adjusted to involve maximum, minimum and intermediate values)
[0036]
[0037]
[0038] A comparative example was set up, and its process parameters are shown in Table 2;
[0039] Table 2 Comparative Example Process Parameters
[0040]
[0041]
[0042] Comparative Example 6 is CoNi ZIF powder, Comparative Example 7 is SnO2 powder, and Comparative Example 8 is BiO2CO3 powder, in order to verify the oxygen evolution ability of a single powder.
[0043] XRD characterization: The XRD pattern of the composite catalyst prepared under the conditions of Example 1 is shown in Figure 1 The diffraction peaks at 10°, 20.6°, 35.8° and 60.8° are the diffraction peaks of CoNi LDH, the diffraction peaks at 16.6°, 24.6° and 29.7° are from Bi2O2CO3, and the diffraction peaks at 34.2° and 45.9° are from SnO2, indicating the successful preparation of CoNi LDH@SnO2@Bi2O2CO3 oxide composite catalyst.
[0044] SEM characterization: SEM images of CoNi ZIF powders are shown in Figure 2. Figure 2 As shown, the sample presents a cubic phase structure with a size of about 500nm and a relatively smooth surface; the BiO2CO3 powder is a flake structure (see Figure 3 ), while SnO2 appears in larger granular form (see Figure 4 ); in CoNi LDH@SnO2@Bi2O2CO3 composite catalyst (see Figure 5 ), the obvious layered morphology of CoNi LDH and the composite structure of SnO2 and Bi2O2CO3 can be observed, which also indicates the successful preparation of the composite catalyst.
[0045] Electrochemical performance characterization:
[0046] A 1.0 M KOH solution was prepared, a graphite electrode was used as a counter electrode, a Hg / HgO electrode was used as a reference electrode, and the catalytic electrodes obtained in Examples 1 to 4 and Comparative Examples 1 to 8 were used as working electrodes. The samples were connected to an electrochemical workstation and subjected to a hydrogen evolution electrochemical performance test. Before the test, the electrodes were activated and the impedance was measured to facilitate subsequent IR compensation. After the test, a reversible hydrogen electrode calibration was performed.
[0047] Taking the catalysts prepared in Example 1, Comparative Example 7 and Comparative Example 8 as examples, the polarization curves are as follows: Figure 6 The test results of Examples 1 to 5 and Comparative Examples 1 to 8 are shown in Table 3;
[0048] Table 3 Electrochemical performance of Examples 1 to 5 and Comparative Examples 1 to 8
[0049]
[0050] The CoNi LDH@SnO2@Bi2O2CO3 composite electrocatalyst prepared in this example has a layered, granular structure, providing a large specific surface area and exposing more active sites. The complementary advantages of different catalysts accelerate electron transport and accumulation at the interface. Phosphating also improves the electronic structure of the catalyst, enhancing catalytic performance and accelerating hydrogen desorption. Furthermore, DC electrodeposition requires simple equipment and is easy to operate, enabling mass production.
[0051] The above describes the specific embodiments of the present invention in detail, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in this field without departing from the scope of the present invention.
Claims
1. A method for preparing a CoNi LDH@SnO2@Bi2O2CO3 oxide composite catalyst, characterized in that: The specific steps are as follows: (1) dissolving cobalt nitrate and nickel nitrate in deionized water to obtain a cobalt-nickel solution, and dissolving dimethylimidazole in deionized water to obtain a dimethylimidazole solution; (2) slowly adding the dimethylimidazole solution to the cobalt-nickel solution under stirring for 10 to 30 minutes, separating the solid and the liquid, and drying the solid to obtain CoNi-ZIF powder; (3) CoNi-ZIF powder was uniformly dispersed in deionized water to obtain a CoNi-ZIF dispersion, SnCl4·5H2O and hexamethylenetetramine were added to the CoNi-ZIF dispersion, stirred for 2-4 h, and then subjected to hydrothermal reaction at 180-200°C for 6-14 h. The solid-liquid separation was performed, and the solid was washed with anhydrous ethanol and then dried to obtain CoNi LDH@SnO2 powder; (4) The CoNi LDH@SnO2 powder was ultrasonically dispersed in deionized water to obtain a CoNi LDH@SnO2 dispersion. Bi(NO3)3·5H2O, hexamethylenetetramine and sodium citrate were added to the CoNiLDH@SnO2 dispersion, and the mixture was stirred and reacted at a temperature of 60-80°C for 2-4 h. The mixture was then placed at a temperature of 140-180°C for hydrothermal reaction for 5-10 h. The solid-liquid separation was carried out, and the solid was dried to obtain the CoNi LDH@SnO2@Bi2O2CO3 oxide composite catalyst.
2. The method for preparing the CoNi LDH@SnO2@Bi2O2CO3 oxide composite catalyst according to claim 1, characterized in that: The mass ratio of cobalt nitrate, nickel nitrate and dimethylimidazole in step (1) is 1:0.5-0.25:15-20, the concentration of cobalt nitrate in the cobalt-nickel solution is 0.004-0.008 g / mL, the concentration of nickel nitrate is 0.002-0.001 g / mL, and the concentration of dimethylimidazole solution is 0.06-0.08 g / mL.
3. The method for preparing the CoNi LDH@SnO2@Bi2O2CO3 oxide composite catalyst according to claim 2, characterized in that: In step (3), the concentration of the CoNi-ZIF dispersion is 0.004-0.002 g / mL, the mass ratio of SnCl4·5H2O to CoNi-ZIF powder is 20-10:1, and the molar ratio of hexamethylenetetramine to SnCl4·5H2O is 0.5-0.6:
1.
4. The method for preparing the CoNi LDH@SnO2@Bi2O2CO3 oxide composite catalyst according to claim 1, characterized in that: Step (4) The concentration of the CoNi LDH@SnO2 dispersion is 0.004-0.002 g / mL, the mass ratio of Bi(NO3)3·5H2O, sodium citrate and CoNi LDH@SnO2 powder is 2.5-6:2-5:1, and the molar ratio of hexamethylenetetramine to Bi(NO3)3·5H2O is 2.5-7.5:
1.
5. CoNi LDH@SnO2@Bi2O2CO3 oxide composite catalyst prepared by the method according to any one of claims 1 to 4.
6. Use of the CoNi LDH@SnO2@Bi2O2CO3 oxide composite catalyst according to claim 5 as a catalyst in hydrogen production by electrolysis of water.